In Indonesia, Hope For The Omnibus Law Method As A Solution To Hyper Regulation - Amirullah Amirullah; Tunggul Anshari SN; Ngesti Dwi Prasetyo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This study aims to describe the expectations of the Omnibus Law Method as a solution to regulatory problems in Indonesia. The research method used is a normative juridical approach with statutory and conceptual approaches. Analytical tools based on the SWOT framework are used to examine primary, secondary, and tertiary sources of law. Due to the overwhelming volume of federal and state laws, the government has chosen to implement sweeping "omnibus" legislation. It's true that rules may be streamlined using the Omnibus approach. One of the goals is the organization of rules, which cannot be achieved if the Formation of Legislation using the Omnibus Law approach is not executed correctly. The success and advantages of the enacted Omnibus Law will determine the future of the method's acceptance in Indonesia's legal system. The regulatory framework is inseparable from the legal underpinnings, apparatus, culture, infrastructure, information technology, and funding that sustain it. The concepts of transparency, caution, and promoting public engagement are essential in Indonesia for applying the Omnibus Law.